The Role of the Rhythm Step on Pro-Agility Test Performance in Division I Football Players. Issue 3 (3rd July 2021) - Papadopoulos, Panayiotis; Lund, Robin J.; Ficklin, Travis K.; Reed, Jacob P.
ABSTRACT: Purpose : The pro-agility test is a common test in multiple sports. A common way to start is the crossover step (CS) where athletes start the drill by crossing one leg over the other. However, the rhythm step (RS), initiated by moving one foot medially before crossing the opposite foot over the first, may result in faster time. Therefore, the purpose of this study was to compare the RS to the CS in the pro-agility test. Methods : Thirteen division I college football players (age 21 ± 1.5 years, mass 103.5 ± 18 kg, and stature 1.87 ± .078 m) were recruited to perform both step techniques. Video was analyzed to determine times during the first five yards (t1 ), the second ten yards (t2 ), the last five yards (t3 ), and the total time (ttotal ). Additionally, maximum acceleration (amax ), time to maximum acceleration (tamax ), maximum body lean angle (θlean ), and time to reach θlean (tθlean ) were measured. Results : Descriptive statistics (mean ± SD) were calculated for all variables. A significant difference between the two techniques was observed at t1 (RS mean 1.56 ± 0.09 s, CS mean 1.62 ± 0.11 s), ttotal (RS mean 4.99 ± 0.35 s, CS mean 5.09 ± 0.35 s), and tamax (RS mean 0.38 ± 0.67, CS mean 0.46 ± 0.61). Conclusion : Overall, the RS appeared to be superior to the CS for reaching peak acceleration faster during the initial phase of the pro-agility drill as well as short distance sprints that are initiated from a standing position.